1985
DOI: 10.1111/j.1748-5827.1985.tb02184.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical staging for oropharyngeal malignancies in the dog

Abstract: One hundred dogs bearing malignancies of the oropharyngeal region were examined over a three‐year period and prospectively staged using the World Health Organisation TNM Classification of Tumours of Domestic Animals. Primary tumours were characterized by their large size or local infiltration (71 per cent, T3 status) and invasion into adjacent bone (60 per cent, Tb status). Regional lymph node metastasis was less common (17 per cent, N1b, N2b or N3 status) and distant metastasis was an unusual presenting featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
2
1

Year Published

1985
1985
2020
2020

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 7 publications
2
12
2
1
Order By: Relevance
“…Whilst this study was not conducted on the basis of a prospectively randomized trial one can compare the actuarial survival rates achieved here with those reported elsewhere for similar groups of oral tumours. The survival rate in this study for the squamous cell carcinomas of 80 per cent bears very favourable comparison with that reported for a similar group of mainly stage I11 squamous cell carcinomas of 44 per cent (White et al, 1985). Data for survival rates of oesteosarcoma of the oral cavity are not available and a direct comparison cannot therefore be made.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Whilst this study was not conducted on the basis of a prospectively randomized trial one can compare the actuarial survival rates achieved here with those reported elsewhere for similar groups of oral tumours. The survival rate in this study for the squamous cell carcinomas of 80 per cent bears very favourable comparison with that reported for a similar group of mainly stage I11 squamous cell carcinomas of 44 per cent (White et al, 1985). Data for survival rates of oesteosarcoma of the oral cavity are not available and a direct comparison cannot therefore be made.…”
Section: Discussionsupporting
confidence: 46%
“…Oral tumours in the dog are frequently complicated by the presence of neoplastic cells in bone (White, Jefferies & Freedman, 1985). For anatomical reasons it has often been considered impractical to excise radically these tumours and treatment had tended to rely on modalities which are suited to the management of the tumour in situ; including radiotherapy, cryosurgery or 'debulking' surgery and their various combinations.…”
Section: Introductionmentioning
confidence: 99%
“…Previous case series have described an improved outcome in dogs receiving radiotherapy for TSCC (MacMillan and others 1982, White and others 1985, Brooks and others 1988, Murphy and others 2006) although results have not necessarily been substantiated statistically by comparison to untreated controls. The small number of animals and the variety in treatment protocols make it difficult to assess the benefit of radiotherapy in this cohort of animals.…”
Section: Discussionmentioning
confidence: 93%
“…Canine tonsillar squamous cell carcinoma (TSCC) is an uncommon disease, representing 9% of canine oral tumours in a UK survey (Bostock and Curtis 1984), and there is relatively limited information regarding presentation, treatment and outcome in the current literature. In contrast to non‐tonsillar SCC, TSCC is characterised by rapid growth, infiltration of underlying tissues and high metastatic potential (Brodey 1970, Todoroff and Brodey 1979, White and others 1985), and is generally regarded to carry a poor prognosis (Brodey 1970, MacMillan and others 1982, Brooks and others 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The biological behaviour of non‐tonsillar SCC and its low metastatic rate generally make surgical resection with wide margins an effective treatment for prolonging survival times and preventing local recurrence (White 1991). The prognosis for non‐tonsillar SCC is strongly correlated to tumour stage, degree of local infiltration, bone involvement and regional and distant metastases, as determined by the World Health Organisation TNM Classification of Tumours of Domestic Animals (White and others 1985). The location of the primary lesion within the oral cavity also determines the efficacy of surgery in achieving complete excision and prevention of local recurrence (Schwarz and others 1991).…”
Section: Discussionmentioning
confidence: 99%